Rancang Bangun Aplikasi Dompet Digital Sederhana Untuk Pencatatan Keuangan Siswa Di Sekolah (Studi Kasus SMP Utama) - Ilham Saputra; Farizi Ilham; Elisa Zahra; M. Zahid Al-Muhdhor (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Financial management among students at SMP Utama has not been conducted in an organized manner. Based on interviews, 57 students across three classes receive daily allowances between IDR 10,000 and IDR 30,000, yet most do not record their income and expenses, potentially reinforcing consumptive spending habits. Most students already own Android smartphones, presenting an opportunity to offer a mobile- based financial management solution. This study aims to design and develop a simple Android -based digital wallet application using the Waterfall development model. The application was built using Android Studio, Java/Kotlin programming language, and Firebase as the real-time data storage backend. Features include account/wallet management, categorized transaction recording, budget management, savings goals, and graphical financial reports. Black Box Testing results confirmed all major application functions operate according to specifications. This application is intended to serve as an effective financial literacy tool for junior high school students.